Răspuns :
[tex]|-\sqrt{3} \,|-|+3\sqrt{3} \,|+|\:2\sqrt{3} +1\,|=[/tex]
[tex]\sqrt{3} -3\sqrt{3} +2\sqrt{3} +1=[/tex]
[tex]\implies-2\sqrt{2} +2\sqrt{2} +1=1[/tex]
__________________________________________
[tex]|\:\sqrt{17} -4\:|+|\:\sqrt{17} -5\:|+|-3\:|[/tex]
[tex]\sqrt{17} -4<0 \implies |\sqrt{17} -4\:|=\sqrt{17} -4[/tex]
[tex]\sqrt{17} -5<0 \implies |\:\sqrt{17} -5\:|=-(\sqrt{17} -5)=-\sqrt{17} +5[/tex]
[tex]\implies \sqrt{17} -4-\sqrt{17} +5+3= -4+5+3=4[/tex]
__________________________________________
[tex]|-2\frac{1}{4} \,|+|+1\frac{3}{4} \,|-|-7\frac{1}{4} \,|=[/tex]
[tex]2\frac{1}{4} +1\frac{3}{4} -7\frac{1}{4} =\frac{2\cdot4+1}{4} +\frac{1\cdot4+3}{4} -\frac{7\cdot4+1}{4}[/tex]
[tex]\implies \frac{9}{4} +\frac{7}{4} -\frac{29}{4} =\frac{9+7-29}{4} =-\frac{13}{4}[/tex]
__________________________________________
[tex]|\:2\sqrt{3} -3\:|+|\:\sqrt{3} -2\:|-|\:\sqrt{3} +1\:|[/tex]
[tex]2\sqrt{3} -3 >0 \implies |\:2\sqrt{3} -3\:|=2\sqrt{3} -3[/tex]
[tex]\sqrt{3} -2<0 \implies |\:\sqrt{3} -2\:|=-(\sqrt{3} -2)=-\sqrt{3} +2[/tex]
[tex]\sqrt{3} +1>0 \implies |\:\sqrt{3} +1\:|=\sqrt{3} +1[/tex]
[tex]\implies 2\sqrt{3} -3+2-\sqrt{3} -(\sqrt{3} +1)=[/tex]
[tex]\implies 2\sqrt{3} -1-\sqrt{3} -\sqrt{3} -1=2\sqrt{3} -2-2\sqrt{3} =-2[/tex]